Dynamic daily associations between insomnia symptoms and alcohol use in adults with chronic pain. (22nd September 2017) - Miller, Mary Beth; Chan, Wai Sze; Boissoneault, Jeff; Robinson, Michael; Staud, Roland; Berry, Richard B.; McCrae, Christina S.
Summary: Individuals with chronic pain are at risk for sleep disruption and heavy alcohol use, yet the daily associations between these behaviours are not well characterized. This study aimed to determine the extent to which alcohol use affects insomnia symptoms and vice versa in adults reporting symptoms of chronic pain. Participants were 73 individuals (93% women) reporting alcohol use in addition to symptoms of insomnia and chronic pain. They completed daily diaries assessing insomnia symptoms and alcohol use for 14 days. Multilevel modelling was used to evaluate the bidirectional associations between alcohol use and insomnia symptoms at the daily level. Consistent with laboratory‐based research, alcohol use was associated with decreased sleep‐onset latency the same night but increased sleep‐onset latency 2 nights later. Specifically, for every alcoholic drink consumed, time to sleep onset decreased by 5.0 min in the same night but increased by 4.3 min 2 nights later. Alcohol use was not significantly associated with subsequent wake after sleep onset or total sleep time, and insomnia symptoms were not significantly associated with subsequent alcohol use. To our knowledge, these data provide the first evidence that alcohol use negatively affects insomnia symptoms up to 2 days post‐consumption in patients reporting symptoms of insomnia and chronic pain. Findings suggest that one drink will have minimal impact on sleep, but heavier drinking (e.g. four–five drinks) may have a clinically significant impact (16–25‐min increase in sleep‐onset latency). Future studies may assess alcohol use as a point of intervention within this population.